(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2021)
In this paper, we study the parallel multicellular dc/ac converter, including monolithic inter-cell transformer (ICT). This structure is very interesting when the ICT is used to ensure the magnetic coupling between the liaison inductances to eliminate the inductances currents ripple. But, if the inductances currents are not equilibrated; the magnetic circuit of the ICT will be saturated, and it causes the dysfunction of the converter. For that, we propose the sliding mode control to regulate the inductances currents. To validate this technique, a real-time simulation is made in using RT-LAB package under MATLAB/SIMULINK of a 7 cells parallel multicellular DC/AC converter including monolithic ICT controlled with sliding mode control.